Trichophyton erinacei kerion barbae from a hedgehog with direct osculatory transfer to another person. (10th September 2013) - Sidwell, R. U.; Chan, I.; Francis, N.; Bunker, C. B.
Summary We describe a case of kerion tinea barbae infection due to Trichophyton erinacei in a 37‐year‐old man. The infection had also been transferred to his partner by direct contact from kissing. T. erinacei is a zoophilic dermatophyte occasionally harboured by the hedgehog (Erinaceus europaeus). There are few reports of human infection in the literature, and it rarely causes a kerion. There is only one previous report of tinea barbae occurrence due to T. erinacei. This case highlights the possibility of one of the more unusual fungal infections that can be acquired in the UK, and highlights the necessity of asking specific questions to identify possible sources of infection.